Phosphor particles, composite and light-emitting device
Patent Information
- Application Number
- JP2023509139
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-26
- Filing Date
- 2022-03-18
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-03-18
AI Technical Summary
【0013】 本発明により、発光特性が良好なフッ化物蛍光体が提供される。
Smart Images

Figure 0007634649000003 
Figure 0007634649000004 
Figure 0007634649000005
Abstract
Description
Technical Field
[0001] The present invention relates to phosphor particles, composites, and light-emitting devices.
[0002] As a phosphor capable of converting blue light emitted from a blue light-emitting diode into red light, a fluoride phosphor represented by K2SiF6:Mn (often abbreviated as "KSF phosphor", etc.) is known. This phosphor is efficiently excited by blue light. Also, the half-value width of the emission spectrum of this phosphor is narrow and sharp. Therefore, by using this phosphor as a red phosphor, a white LED with high brightness and excellent color rendering properties and color reproducibility can be realized.
[0003] As a prior art of fluoride phosphors, for example, Patent Document 1 can be cited. Patent Document 1 describes a fluoride phosphor having a composition represented by the general formula A2MF6:Mn, a bulk density of 0.80 g / cm3 or more, and a mass median diameter of 30 μm or less. In the general formula, 0 < n ≦ 0.1, element A is one or more alkali metal elements containing K, and element M is Si alone, Ge alone, or a combination of one or more elements selected from the group consisting of Si and Ge, Sn, Ti, Zr, and Hf. (1-n) F6:Mn 4+ n represented by, and a bulk density of 0.80 g / cm 3 or more, and a mass median diameter of 30 μm or less is described. In the general formula, 0 < n ≦ 0.1, element A is one or more alkali metal elements containing K, and element M is Si alone, Ge alone, or a combination of one or more elements selected from the group consisting of Si and Ge, Sn, Ti, Zr, and Hf.
[0004] Also, Patent Document 2 can be cited as a prior art of fluoride phosphors. Patent Document 2 describes a phosphor characterized by comprising a crystal having a structure in which a transition metal is substituted as an activator in a part of a host crystal represented by A2BF6 (where A is K, Na, Rb, or Cs, and B is Si, Ge, Sn, Ti, or Zr, excluding combinations of K and Si, K and Ge, and K and Ti).
Prior Art Documents
Patent Documents
[0005]
Patent Document 1
[0006] As white LEDs become more widespread, there is a demand for further improvement in the luminescence properties of fluoride phosphors.
[0007] The present inventors have carried out various investigations with the aim of obtaining a fluoride phosphor having good luminescence characteristics. [Means for solving the problem]
[0008] The present inventors have completed the invention provided below and have solved the above problems.
[0009] According to the present invention, there is provided the following phosphor particles.
[0010] A phosphor particle having a composition represented by the following general formula (1): A phosphor particle having at least one microscopic depression on its surface. General formula (1):A2MF6:Mn In the general formula (1), Element A is one or more alkali metal elements containing K, The element M is a single element of Si, a single element of Ge, or a combination of Si and one or more elements selected from the group consisting of Ge, Sn, Ti, Zr, and Hf.
[0011] Further, according to the present invention, A composite material comprising the above phosphor powder and a sealing material that seals the phosphor powder. is provided.
[0012] Further, according to the present invention, A light-emitting device comprising a light-emitting element that emits excitation light and the above-mentioned composite that converts the wavelength of the excitation light. is provided. Effect of the Invention
[0013] The present invention provides a fluoride phosphor having good luminescence properties. [Brief description of the drawings]
[0014] [Figure 1] FIG. 4 is a diagram for explaining the shape of minute recesses. [Diagram 2] FIG. 1 illustrates an example of a light emitting device. [Diagram 3] 1 is an electron microscope image of the phosphor particles produced in Example 1. [Figure 4] 1 is an electron microscope image of phosphor particles produced in Example 2. [Diagram 5] 1 is an electron microscope image of phosphor particles produced in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. All drawings are for illustrative purposes only. The shapes and dimensional ratios of each member in the drawings do not necessarily correspond to the actual articles.
[0016] <Phosphor particles> The composition of the phosphor particles of this embodiment is represented by the following general formula (1): With this composition, the phosphor particles of this embodiment convert the blue light normally emitted from a blue LED into red light. General formula (1):A2MF6:Mn In the general formula (1), Element A is one or more alkali metal elements containing K, The element M is a single element of Si, a single element of Ge, or a combination of Si and one or more elements selected from the group consisting of Ge, Sn, Ti, Zr, and Hf.
[0017] In terms of "shape," the phosphor particle of this embodiment has at least one minute recess on its surface.
[0018] It is presumed that when blue light is irradiated onto the phosphor particles of this embodiment, the blue light "penetrates" into the minute recesses, and is converted into red light without waste. This is presumed to improve the light emission characteristics.
[0019] The phosphor particles of this embodiment can be manufactured by using appropriate raw materials and adopting appropriate manufacturing methods and manufacturing conditions. The manufacturing method will be described in detail later, but the phosphor particles of this embodiment can be obtained by appropriately selecting and controlling the order in which various raw materials are added to water and the temperature at which they are added when precipitating the phosphor particles in water.
[0020] The phosphor particles of this embodiment will be described further.
[0021] (Regarding the shape of the micro recesses) Examples of specific shapes of the micro recesses are shown in microscope images in the Examples section given later, but for the purpose of explanation, FIG. 1 shows a schematic diagram of the micro recesses and their vicinity.
[0022] 1, the micro recesses are present on a substantially planar surface of a phosphor particle. The micro recesses may be present in a substantially planar portion of the phosphor particle surface, or may be present in a non-planar portion of the phosphor particle surface. 1, the micro recesses become smaller as they become deeper, but the micro recesses are not limited to this form. The micro recesses may have an approximately constant diameter in the depth direction, for example, like a well. The depth of the minute recess, that is, the distance between the surface of the phosphor particle and the bottom of the minute recess, is preferably 0.5 μm or more and 20 μm or less, and more preferably 1 μm or more and 10 μm or less.
[0023] The shape of the opening of the micro recess, i.e., the "edge" of the micro recess on the surface of the phosphor particle, is not particularly limited, but is preferably triangular. The "triangular shape" here does not have to be a mathematically strict triangular shape, but may be any shape that can be recognized as a triangle from a common sense point of view. For example, some or all of the three sides of the triangle do not have to be strictly straight lines. The triangle may be an equilateral triangle, an isosceles triangle, or a triangle with all three sides of different lengths.
[0024] The maximum diameter of the opening of the minute recess is preferably 0.5 μm to 20 μm, more preferably 1 μm to 10 μm. The maximum diameter is determined by measuring the maximum diameter of the opening in a two-dimensional image of the phosphor particle taken by an electron microscope. The maximum diameter of the opening in a two-dimensional image of phosphor particles captured by an electron microscope varies depending on the direction of the captured phosphor particles. However, even in consideration of this variation, better light emission characteristics can be obtained if the maximum diameter falls within the above numerical range. In other words, the above numerical range of 1 μm to 20 μm is a numerical range that takes into consideration the variation in the maximum diameter that differs depending on the direction in which the phosphor particles are captured.
[0025] (About particle aggregation) The phosphor particles of this embodiment may be primary particles or secondary particles formed by agglomeration of primary particles. In other words, the phosphor particles of this embodiment may be secondary particles having minute recesses on the surfaces thereof. Generally, when phosphor particles are secondary particles, their light emission characteristics tend to deteriorate. However, the phosphor particles of this embodiment have minute recesses, which may suppress the deterioration of the light emission characteristics.
[0026] (Regarding the size of the particles themselves) The major axis of the phosphor particles of this embodiment, as determined from an image taken by an electron microscope, is preferably 3 μm to 150 μm, more preferably 5 μm to 100 μm, and even more preferably 10 μm to 50 μm. By having this major axis of an appropriate size, better light emission characteristics can be obtained. An image of phosphor particles taken by an electron microscope is a two-dimensional image, and the major axis varies depending on the direction of the phosphor particles photographed. However, even in consideration of this variation, better light emission characteristics can be obtained if the major axis falls within the above numerical range. In other words, the above numerical range of 3 μm or more and 150 μm or less is a numerical range that takes into consideration the variation in the major axis, which differs depending on the direction in which the phosphor particles are photographed.
[0027] (Composition: General formula (1)) The element A is one or more alkali metal elements containing K. Specifically, it may be K alone or a combination of K and one or more alkali metal elements selected from Li, Na, Rb, and Cs. From the viewpoint of chemical stability, it is preferable that the content of K in the element A is high (for example, 50 mol % or more of K in the element A), and it is more preferable that the element A is a single element.
[0028] The element M is Si alone, Ge alone, or a combination of Si and one or more elements selected from the group consisting of Ge, Sn, Ti, Zr, and Hf. From the viewpoint of chemical stability, it is preferable that the content of Si in the element M is high (for example, 50 mol % or more of Si in the element M), and it is more preferable that the element M is Si alone.
[0029] (Ratio of phosphor particles having micro-depressions in phosphor powder) When phosphor particles are applied to the composite body or light emitting device described below, phosphor powder, which is an aggregate of phosphor particles, is usually used. The ratio of phosphor particles having at least one micro recess on the surface in the phosphor powder is, for example, 10% or more, preferably 30% or more, more preferably 50% or more, and even more preferably 75% or more, based on the number of particles. This value can be determined, for example, by checking whether at least 50 phosphor particles in an electron microscope image have a micro recess.
[0030] The cumulative 50% value in the volume-based particle size distribution curve of the phosphor powder is D 50 Then, D 50is preferably 10 μm or more and 40 μm or less, more preferably 20 μm or more and 35 μm or less. 50 When the value of is appropriate, it is easy to obtain sufficient quantum efficiency, and when it is necessary to mix the phosphor powder with a resin or the like to form a film or sheet containing the phosphor for LED packaging purposes, it is easy to form a uniform and smooth film or sheet.
[0031] In addition, the cumulative 10% value in the volume-based particle size distribution curve of the phosphor powder is D 10 , cumulative 50% value D 50 , cumulative 90% value D 90 Then, (D 90 -D 10 ) / D 50 is preferably 1.2 or less, more preferably 0.9 or less, and even more preferably 0.75 or less. There is no particular lower limit, but it is, for example, 0.3 or more, specifically 0.5 or more. (D 90 -D 10 ) / D 50 can be considered as an index showing the "width" of the particle size distribution. A narrow width of the particle size distribution of a phosphor powder means that the particle sizes of the phosphor particles in the phosphor powder are relatively "uniform". Therefore, (D 90 -D 10 ) / D 50 By keeping the ratio of the phosphor powder to 0.9 or less, it is easy to form a uniform and smooth film or sheet when it is necessary to form a film or sheet containing the phosphor by mixing the phosphor powder with a resin or the like. Also, nozzle clogging can be suppressed in the manufacture of LED packages. The volume-based particle size distribution curve can be obtained through measurement by a laser diffraction scattering method. For details of the measurement method, see the examples given later.
[0032] <Method of manufacturing phosphor particles> The phosphor particles of this embodiment can be manufactured by using an appropriate material and selecting an appropriate manufacturing method and manufacturing conditions. A preferred manufacturing procedure will be described below. It is presumed that by adopting the following procedure, localized highs and lows in the degree of supersaturation during crystal growth will probably occur, causing the growth rate to change, resulting in the formation of minute recesses.
[0033] (1) Preparation of hydrofluoric acid Hydrofluoric acid (aqueous solution of HF) is placed in a corrosion-resistant container to prepare the solution. The concentration of hydrogen fluoride is preferably 50 to 60 mass %.
[0034] (2) Cooling the hydrofluoric acid and adding KHF2 While cooling the hydrofluoric acid prepared in (1) above, KHF2 is added and stirred. Then, while continuing stirring, the inside of the beaker is cooled. Cooling is preferably performed until the temperature inside the beaker is between -35°C and 0°C, more preferably between -15°C and -2°C, and even more preferably between -10°C and -5°C. According to the knowledge of the present inventors, by cooling the inside of the beaker in this manner and then performing the steps from (3) below, the way in which the crystals grow is controlled, making it easier to obtain phosphor particles having minute recesses.
[0035] In addition, when carrying out the steps from (3) onwards, cooling may be continued, or cooling may be stopped and the temperature may be gradually brought closer to room temperature. Theoretically, the former is considered preferable because it is easier to control various factors, but the latter has the advantage in terms of manufacturing costs (energy savings).
[0036] (3) Simultaneous feeding of raw materials containing Mn and raw materials containing Si In the beaker cooled in (2) above, the raw material containing Mn and the raw material containing Si are simultaneously added and stirred. Although the details are unclear, the "simultaneous addition" of the two raw materials may also be related to the formation of micro-depressions in the phosphor particles.
[0037] Examples of raw materials containing Mn include hexafluoromanganates, permanganates, oxides (except permanganates), fluorides (except hexafluoromanganates), chlorides, sulfates, and nitrates. Among them, fluorides are preferred because they can efficiently substitute Mn for the Si site in the fluoride phosphor and provide good luminescence characteristics, and among fluorides, hexafluoromanganates are preferred. Examples of hexafluoromanganates include Na2MnF6, K2MnF6, and Rb2MnF6. In particular, K2MnF6 is preferred because it contains F and K (corresponding to element A) that constitute fluoride phosphors in addition to Mn. A preferred example of the raw material containing Si is SiO2. SiO2 is preferred as the raw material containing Si because it is easily available and can be easily obtained at high purity.
[0038] (4) Adding raw materials containing Mn (preferably in multiple batches) In the above (3), the two raw materials are added and stirred for 30 to 60 seconds, and then the raw material containing Mn is added to the beaker. It is preferable to charge the raw material containing the required amount of Mn in several times (preferably about 2 to 5 times). This is believed to homogenize the element composition in the phosphor particles (avoiding uneven distribution of Mn in the center). This is preferable in terms of further improving the light emission characteristics. Specific examples of the raw material containing Mn are as explained in (3) above.
[0039] The obtained phosphor particles are collected by solid-liquid separation such as by filtration, and washed with an organic solvent such as methanol, ethanol, or acetone. If a fluoride phosphor is washed with water, some of it may be hydrolyzed to produce a brown manganese compound, which may deteriorate the properties of the phosphor. For this reason, it is preferable to use an organic solvent in the washing process. Furthermore, washing with hydrofluoric acid reaction solution several times before washing with an organic solvent can dissolve and remove trace amounts of impurities that have been generated. The concentration of hydrofluoric acid in the hydrofluoric acid reaction solution used for washing is preferably 5% by mass or more from the viewpoint of suppressing decomposition of the fluoride phosphor, and is preferably 60% by mass or less from the viewpoint of phosphor solubility. After the washing step, it is preferable to thoroughly evaporate the washing solution by drying. In addition, classification may be performed using a sieve with a specified mesh size, and coarse particles may be removed.
[0040] <Composite, light-emitting device> The composite of this embodiment includes the above-mentioned phosphor particles and a sealant that seals the phosphor particles. Moreover, the light emitting device of the present embodiment includes a light emitting element that emits excitation light, and the above-mentioned composite that converts the wavelength of the excitation light. The light emitting device of this embodiment is preferably used as, for example, a backlight for a display.
[0041] An example of the composite and the light emitting device will be described below with reference to FIG.
[0042] FIG. 2 is a schematic diagram of the light emitting device 1. As shown in FIG. The light emitting device 1 includes a composite 10 and a light emitting element 20. The composite 10 is provided in contact with an upper portion of the light emitting element 20. The light emitting element 20 is typically a blue LED. Terminals are provided on the bottom of the light emitting element 20. When the terminals are connected to a power source, the light emitting element 20 can emit light. The excitation light emitted from the light emitting element 20 is wavelength converted by the complex 10. When the excitation light is blue light, the blue light is wavelength converted to red light by the complex 10 containing phosphor particles.
[0043] The composite 10 can be composed of the above-mentioned phosphor particles and a sealant that seals the phosphor powder. The composite 10 may further contain phosphor particles other than the above-mentioned phosphor particles. As the sealing material, for example, various curable resin materials (materials that are cured by heat and / or light) can be used. Any curable resin material can be used as long as it is sufficiently transparent and can provide the optical properties required for a display or lighting device. Examples of the sealing material include silicone resin materials. Regarding silicone resin materials, curable materials are supplied by Toray Dow Corning Co., Ltd., Shin-Etsu Chemical Co., Ltd., etc., and silicone resin materials are preferable from the viewpoints of high transparency and excellent heat resistance. In addition, examples of the sealing material include epoxy resin materials and urethane resin materials. The amount of phosphor particles (including the above-mentioned phosphor particles and phosphor particles other than the above-mentioned phosphor particles) in the composite 10 is, for example, 10 to 70 mass %, preferably 25 to 55 mass %.
[0044] There is no particular limitation on the size or shape of the light-emitting element 20. Depending on the application of the light-emitting device 1, the light-emitting element 20 can have any size or shape.
[0045] 2 is a so-called chip-type light-emitting device. The light-emitting device to which the phosphor particles of the present embodiment are applied is not limited to the chip-type, and may be a bullet-type, a multi-segment type, or the like.
[0046] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES
[0047] The embodiments of the present invention will be described in detail based on Examples and Comparative Examples. It should be noted that the present invention is not limited to the Examples.
[0048] <Raw materials> The following raw materials were used: HF: Aqueous solution with a concentration of 55% by mass manufactured by Stella Chemifa Corporation K2SiF6: manufactured by Morita Chemical Co., Ltd. K2MnF6: Prepared by the method described in paragraph 0042 of JP2019-001897A KHF2: Special grade reagent manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. SiO2: FB-50R manufactured by Denka Co., Ltd.
[0049] <Production of phosphor particles> Example 1 The phosphor particles were produced according to the following procedure. (1) At room temperature, 2100 mL of an aqueous HF solution with a concentration of 55% by mass was placed in a Teflon (registered trademark) beaker. (2) While cooling the HF aqueous solution, 2315 g of KHF was added and stirred. While continuing to stir, the mixture was cooled until the temperature inside the beaker reached -7°C. (3) 64 g of K2MnF and 72 g of SiO2 were simultaneously added to a beaker at -7°C and stirred for 45 seconds. (4) While continuing to cool at -7°C, 4 g of K2MnF was added to the beaker and stirred for 45 seconds. (5) While continuing to cool at -7°C, 64 g of K2MnF was further added to the beaker and stirred for 45 seconds. (6) While continuing to cool at -7°C, 64 g of K2MnF was further added to the beaker and stirred for 25 minutes.
[0050] After the stirring was completed, the solution was left to stand to precipitate the yellow solids. After the precipitation was confirmed, the supernatant was removed, and the yellow solids were washed with hydrofluoric acid having a concentration of about 24% by mass, and then washed with methanol. The washed solids were filtered to separate and recover the solids, and further dried to evaporate and remove the remaining methanol. After the drying process, a nylon sieve with 75 μm openings was used to classify and recover only the yellow powder that passed through the sieve. In this manner, phosphor particles were obtained.
[0051] Example 2 Phosphor particles were obtained in the same manner as in Example 1, except that the cooling was stopped between (2) and (3) above, i.e., from (3) above onwards, the temperature in the beaker was allowed to gradually and naturally approach room temperature.
[0052] Fig. 3 shows an electron microscope image of the phosphor particles obtained in Example 1. Fig. 4 shows an electron microscope image of the phosphor particles obtained in Example 2. As shown in the respective electron microscope images, in Examples 1 and 2, phosphor particles having minute recesses on the surface were obtained. As can be seen from each electron microscope image, many of the micro recesses had triangular openings. The maximum diameter of the openings confirmed from each electron microscope image (if the openings were triangular, the length of the longest side of the triangle) was within the range of approximately 1 μm to 20 μm. Specifically, the maximum diameter of the triangular openings of the particles circled in Figure 3 was approximately 5 μm. Also, the maximum diameter of the triangular openings of the particles circled in Figure 4 was approximately 9 μm. Moreover, secondary particles formed by aggregation of primary particles were confirmed from each electron microscope image, and minute recesses were also confirmed on the surfaces of the secondary particles. Furthermore, in each of the microscopic images, the major axis of the phosphor particles having microscopic recesses on their surfaces was within the range of approximately 10 μm to 100 μm.
[0053] Comparative Example 1 With reference to the description in Patent Document 2 (WO 2009 / 119486), phosphor particles were obtained according to the following procedure. The following procedure was carried out at room temperature. (1) First, 100 mL of an aqueous HF solution (46-48%), 6 g of KMnO4, and 100 mL of H2O were mixed to obtain a solution. (2) 0.38 g of a Si wafer having a thickness of 0.635 mm cut from an n-type dummy wafer was placed in the above solution and allowed to stand for 48 hours. (3) After the solution was left to stand, the supernatant was removed, and the remaining solid matter (precipitated crystals and the undissolved Si wafer) was washed with methanol. The undissolved Si wafer was then manually removed. In this manner, a phosphor powder was obtained.
[0054] FIG. 5 shows an electron microscope image of the obtained phosphor particles, but no minute recesses with openings as in FIGS. 3 and 4 could be confirmed.
[0055] <Identification: Crystal phase measurement, composition measurement, etc.> For the phosphor powder (yellow powder) obtained in each example, an X-ray diffraction pattern was obtained using an X-ray diffractometer. The obtained X-ray diffraction pattern was the same as that of K2SiF6 crystal. From this, it was confirmed that K2SiF6:Mn was obtained in a single phase.
[0056] <Particle size distribution measurement by laser diffraction scattering method> 30 mL of ethanol was measured into a 50 mL beaker, and 0.03 g of phosphor powder was added thereto. Next, the container was placed in a homogenizer (manufactured by Nippon Seiki Seisakusho, product name US-150E) whose output had been adjusted to "Altitude: 100%" in advance, and pretreatment was carried out for 3 minutes. The volume-based particle size distribution curve was obtained for the solution thus prepared using a laser diffraction scattering type particle size distribution analyzer (manufactured by Microtrackbell, product name MT3300EXII). 10 , D 50 and D. 90 Also,
[0057] [Table 1]
[0058] <Evaluation of light emission characteristics (quantum efficiency, etc.)> A standard reflector (Spectralon, product name, manufactured by Labsphere) with a reflectance of 99% was set at the side opening (φ10 mm) of an integrating sphere (φ60 mm). Monochromatic light, which was split into 455 nm wavelengths from a light emission source (Xe lamp), was introduced into this integrating sphere via an optical fiber, and the spectrum of the reflected light was measured with a spectrophotometer (MCPD-7000, product name, manufactured by Otsuka Electronics Co., Ltd.). At this time, the number of excitation light photons (Qex) was calculated from the spectrum in the wavelength range of 450 to 465 nm. Next, the phosphor powder obtained in each Example was filled in a concave cell so that the surface was smooth, and the cell was set in the opening of an integrating sphere, and monochromatic light with a wavelength of 455 nm was irradiated, and the excitation reflected light and fluorescence spectra were measured by a spectrophotometer. The number of excitation reflected light photons (Qref) and the number of fluorescence photons (Qem) were calculated from the obtained spectrum data. The number of excitation reflected light photons was calculated in the same wavelength range as the number of excitation light photons, and the number of fluorescence photons was calculated in the range of 465 to 800 nm. From the obtained three types of photon numbers, the absorptivity (=(Qex-Qref) / Qex×100), internal quantum efficiency (=Qem / (Qex-Qref)×100), and external quantum efficiency (=Qem / Qex×100) were calculated.
[0059] The above results are summarized in Table 2.
[0060] [Table 2]
[0061] As shown in the above table, the light emitting properties of the phosphor particles of Examples 1 and 2 were good.
[0062] This application claims priority based on Japanese Patent Application No. 2021-052759, filed on March 26, 2021, the disclosure of which is incorporated herein in its entirety.
Claims
1. A phosphor particle having a composition represented by the following general formula (1): having at least one micro recess on its surface; At least one of the micro recesses has an opening having a maximum diameter of 1 μm or more and 20 μm or less, A phosphor particle having a cumulative 10% value D 10 , a cumulative 50% value D 50 and a cumulative 90% value D 90 in a volume-based particle size distribution curve obtained by a laser diffraction scattering method, the ratio (D 90 -D 10 ) / D 50 being 1.2 or less. General formula (1): A 2 MF 6 :Mn In general formula (1), Element A is one or more alkali metal elements containing K, The element M is Si alone, Ge alone, or a combination of Si with one or more elements selected from the group consisting of Ge, Sn, Ti, Zr, and Hf.
2. 2. The phosphor particle according to claim 1 , The phosphor particle, wherein the opening of the minute recess has a triangular shape.
3. 3. The phosphor particle according to claim 1, Phosphor particles are secondary particles formed by agglomeration of primary particles.
4. A composite comprising the phosphor particles according to any one of claims 1 to 3 and a sealing material that seals the phosphor particles.
5. A light emitting device comprising: a light emitting element that emits excitation light; and the composite according to claim 4 that converts the wavelength of the excitation light.
Citation Information
Patent Citations
Fluophor and manufacturing method therefor, fluophor-containing composition and light-emitting device using fluophor, and image display unit and luminaire using light-emitting device
JP2018178129A
Fluoride phosphor and light-emitting device using the same
JP2019001897A
Fluorescent material, process for producing the same, and white-light-emitting diode employing the fluorescent material
WO2009119486A1
Process for producing fluorescent material
WO2016133110A1